GADHON SALIN SWARA: INTERPRETASI GAMELAN GADHON - Laurentius Hanan; Wahyu Thoyyib Pambayun (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2023)
This article recounts the author's experience in the process of composing